STOMACH CONTENTS AND INDEX OF FOOD SIGNIFICANCE OF OREOCHROMIS NILOTICUS (L.) IN KIRI RESERVOIR, SHELLENG, ADAMAWA STATE, NIGERIA (FULafia Journal of Science and Technology, 2019)
Studies on natural feeding of fish to identify the trophic relationships present in aquatic ecosystems, identifying feeding composition, structure and stability of food webs was carried out. The study was designed to generate a baseline information on the food and feeding habits of Oreochromis niloticus, in Kiri reservoir, Shelleng LGA, Adamawa State, Nigeria. Sampling was done twice in a month for a period of six months from May to October 2015. On the landing site, fish specimen were randomly sorted and identified using keys. In the laboratory, each specimen was dissected using a pair of scissors to remove the gut. The entire stomach of the fish was removed and graded according to fullness. Stomach contents was sorted into categories and analyzed using Relative Frequency (RF) and point’s method. % RF and % PP (Percentage of total Points) was then used to determine the Index of Food Significance IFS. The major food items in terms of frequency of occurrence were Pithopora (55.71%), while insect parts has the lowest frequency of occurrence with 15.70%. The Index Food Significance (IFS) of O. niloticus showed that Filamentous Algae and Colonial Green Algae are the secondary diet of the fish species in Kiri Reservoir, with Cladophora (IFS= 1.04%) Pithopora (IFS=1.06%) and Volvox (IFS=1.45%), Green Algae, Cyanobacteria and Diatom are among the incidental diet, with an IFS
Keywords: Stomach Content; Index of Food Significance; Oreochromis niloticus; Kiri Reservoir; Shelleng